Towards A Resilient Healthcare: Experiential Insights on Vaccination Importance among Rural Communities in Indonesia and Philippines - Hamidah; Joel A Roy; Deasy Silvya Sari; Nursiswati (Universitas STRADA Indonesia, 2025)
Background: People's perceptions of the need for COVID-19 vaccine boosters are influenced by a variety of psychosocial, demographic, and informational factors. Indonesia and Philipines data might be show difference people’s perception to response the important of booster vaccinations. Purpose: This study aims to describe the differences between two difference population from two countries namely Indonesia and the Philipines. This is descriptive study with two datasets from respondents in Indonesia anad the Philipines. Methods: This research explore perceptions on vaccination and the willingness to get second shoots of covid-19 vaccination. A total 101 respondent from Indonesia and 400 respondents from the Philipines included in this study. Sample method was consecutive. Results: The result showed that 57% received covid-19 booster, while 43 43% have not received the Covid 19 booster vaccine. From the Philipines’data, 29% of respondents have received the Covid 19 booster vaccine, while 71% have not received the Covid 19 vaccine. Indonesian data shows that 76% think that booster vaccines can increase body immunity, extend the period of protection against the virus and help reduce the spread of the Covid 19 virus. Conclusion: Meanwhile, Filipino data shows various perceptions underlying the willingness to do the covid-19 booster vaccine, namely the existence of local government policies in providing vaccines as much as 93%, the adequacy of vaccine supply 76%, It is concluded that percentage of covid 19 booster participation among two countries quiet difference and the perception show based on people perception on resilience during pandemi and support from health care system.